Entrepreneurial university ecosystem's engagement with SDGs: looking into a Latin-American University. (4th May 2023) - Guerrero, Maribel; Lira, Matías
ABSTRACT: Sustainability themes have increasingly gained traction within academia and industry. The knowledge accumulation is at the development stage and remains more understanding about the phenomenon in the black box. Innovative sustainable initiatives are little known, especially in transforming individuals' values, culture, and well-being. Universities are well-placed to contribute to this academic conversation as they seek solutions and responses to current grand societal challenges through their core activities (teaching, research, and engagement). A good example has been the recent development of disruptions by universities to address the COVID-19 pandemic. Inspired by these debates, this study theorizes/tests how an entrepreneurial university ecosystem contributes to the UN SDGs' achievement through its core activities and social-entrepreneurial orientation. By adopting a retrospective case study of a Latin-American University, our study provides insights/implications into the configuration of university social entrepreneurial ecosystems and their sustainable contributions to the SDGs.